PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 1 BENGKALIS - Novitasari Novitasari; Syahrilfuddin Syahrilfuddin; Lazim.N Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The low yield learning mathematics is the basis why the research was conducted. This research is a classroom action research that aims to improve math learning result fourth grade students of SD Negeri 1 Bengkalis. The number of subjects in this research is 34 people. The instrument of collecting data in this research is the observation sheet activities of teachers and students and test questions. The results showed that the application of learning models Team Assisted Individualization (TAI) can increase the activity of teachers and students and students' math learning result. At the first meeting of the first cycle, the activities of teachers rated at 45.83%. At the next meeting, the activities of teachers be 66.67%. At the first meeting of the second cycle, the activities of teachers percentage increased to 83.33%. At the second meeting be 91.67%. At the first meeting of the first cycle, the percentage of student activity amounted to 45.83%. At the next meeting, increased to 66.67%. In the second cycle the first meeting, the percentage of student activity amounted to 79.17%. And the second meeting be 91.67%. Before action is taken, the average value of student learning result at 62.27. In the first cycle, the average student learning result increased to 71.06, an increase of 14.12%. In the second cycle, the average value of student learning result be 78.03, an increase of 25.31%.Keyword: Learning models Team Assisted Individualization (TAI), Math learning result.